Analisis Laju Korosi Baja St37 dengan Inhibitor Ekstrak Daun Jambu Biji dalam Medium Korosif HCl 3% pada Suhu 80°C dan 100°C - Putri Vidia Citra; Ediman Ginting Suka; Agus Riyanto (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
This study aims to determine the effectiveness of guava leaf extract as an inhibitor of St37 steel in 3% HCl corrosive medium. Weight reduction method is used to determine the value of the resulting corrosion rate. Soaking of St37 steel at 80 ° C and 100 ° C was carried out with variations in the addition of 0%, 4%, and 8% inhibitor concentrations. The results show the lowest corrosion rate is at a concentration of 8% at an immersion temperature of 80 ° C with an inhibitor efficiency value of 84.07%. Fourier transform infra red (FTIR) analysis results showed that tannin content was found in guava leaf extract. The x-ray diffraction (XRD) results show that the phase formed is pure Fe phase. The results of scanning electron microscopy (SEM) show the presence of lumps on steel surfaces of various sizes which are the product of corrosion. This is reinforced by the results of energy dispersive spectroscopy. (EDS) which shows that the increasing number of lumps on the steel surface leaves fewer Fe elements and more FeO corrosion products.